Quantitative comparison of macular segmentation performance using identical retinal regions across multiple spectral-domain optical coherence tomography instruments. Issue 6 (6th January 2015) - Waldstein, Sebastian M; Gerendas, Bianca S; Montuoro, Alessio; Simader, Christian; Schmidt-Erfurth, Ursula
Abstract : Purpose: Comparison of optical coherence tomography (OCT) segmentation performance regarding technical accuracy and clinical relevance. Methods: 29 eyes were imaged prospectively with Spectralis (Sp), Cirrus (Ci), 3D-OCT 2000 (3D) and RS-3000 (RS) OCTs. Raw data were evaluated in validated custom software. A 1 mm diameter subfield, centred on the fovea, was investigated to compare identical regions for each case. Segmentation errors were corrected on each B-scan enclosed in this subfield. Proportions of wrongly segmented A-scans were noted for inner and outer retinal boundaries. Centre point thickness (CPT) and central macular thickness (CMT) were compared before and after correction. Results: Segmentation errors occurred in 77% and affected on average 29% of A-scans, resulting in mean differences of 24/13 µm (CPT/CMT). The incidence of segmentation errors was 48% (Sp), 79% (Ci), 86% (3D) and 93% (RS), p<0.001. Mean proportions of A-scans with wrong outer retinal boundary were 30% (Sp), 9% (Ci), 23% (3D) and 10% (RS), p=0.006; proportions for the inner retinal boundary were 11% (Sp), 12% (Ci), 6% (3D) and 21% (RS), p=0.034. Mean deviations in CPT/CMT were 41/28 µm (Sp), 17/11 µm (Ci), 30/13 µm (3D) and 18/8 µm (RS), p=0.409/0.477. Conclusions: By comparison of identical regions, substantial differences were detected between the tested OCT devices regarding technical accuracy and clinical impact. Spectralis showed lowest error incidence but highest error impact.